Entrepreneurship and Privatization in Central Europe: The Tenuous Balance Between Destruction and Creation - Spicer, Andrew; McDermott, Gerald A.; Kogut, Bruce (Academy of Management Review, 2000)
Andrew Spicer, Gerald A. McDermott, Bruce Kogut, Entrepreneurship and Privatization in Central Europe: The Tenuous Balance between Destruction and Creation, The Academy of Management Review, Vol. 25, No. 3 (Jul., 2000), pp. 630-649